Impact of Classroom Emotional Intelligence on Self-Esteem andAcademic Achievement of Students at Secondary Level (Journal of Asian Development Studies, 2023)
Emotional intelligence in the classroom is a crucial area of research in many academic disciplinesregarding secondary students' academic achievement and self-worth in the Dera Ismail Khandistrict of Pakistan. The study's main objective was to assess CEI's impact on students' SE. Thesecond objective was to ascertain the effects of emotional intelligence in the classroom on theacademic performance of secondary school students. A total of 20 secondary schools were selectedfrom both rural and urban areas of Dera Ismail Khan. The population consisted of 49000secondary school students. The sample of study 490 was comprised of 276 science students and215 art students. Two questionnaires were constructed, i.e., the classroom emotional intelligencequestionnaire (CEIQ) and the self-esteem questionnaire (SEQ). Fifteen educational expertsvalidated all items of both CEIQ and SEQ. Still, the reliability of the data was assessed using theCronbach alpha test. The dependability of the EI was 0.811, and the SE was 0.801. The findingsof the study reveal that there is a positive relationship between classroom emotional intelligencewith self-esteem (r=.06**) and the academic achievement of students (r=.58**). The studyrecommended that students be given more resources and encouragement to express theirdestructive emotions before they label them with any undesirable characteristics.